Open access como marco licitatório para concessões ferroviárias: estudo de caso da ligação Açailândia-Barcarena - Souza, Jéssyka Wisnieski (2017)
This work evaluated the project of Açailândia-Barcarena rail link under the Open Access model, seeking ways to make its concession feasible, especially through the application of new perceptions defended by the Territorial Engineering, such as: the association of activity centers that add value to the products; and the combination of public and private initiatives for regional development. To this end, the work approached theoretical and bibliographical aspects regarding the techniques pertinent to the research development, the contextualization of the Open Access model in different countries and the essential information of the railway corridor. The method of analysis was applied in order to mitigate the inconveniences of the Open Access model. The necessary demand for the project feasibility was estimated. In addition, the sensitivity analysis was performed by varying discount rates and demands with values between the minimum estimated and the maximum limited by the railway capacity, which allowed the perception of the optimum demand of the project and obtaining the maximum benefits of the rail link under the projected conditions and under the new regulatory framework. In the end, among other considerations regarding the Açailândia-Barcarena feasibility, the work proposes an initial Program of Economic Consolidation according to the Territorial Engineering perspective.